Think Globally, Act Locally: Strategi Bisnis Digital Kreatif dan Inovatif - Sigit Pramono Hadi; Seger Santoso; Isna Wati (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
In the ever-evolving digital era, the concept of "Think Globally, Act Locally" emerges as a key strategy for managing creative and innovative digital businesses. This study aims to explore how companies can integrate global approaches with local adaptations to enhance business competitiveness. The research method involves literature analysis, interactive discussions in webinars, and case studies on digital strategy implementation. Findings reveal that the success of digital businesses is highly influenced by their adaptability to local market needs while maintaining a global vision. The study implies the significance of innovation and creativity in developing culturally relevant products and services, along with leveraging digital technology as a strategic tool. Strategies combining local and global perspectives have the potential to foster sustainable business growth.